Borderline intellectual functioning and psychosis: Adult Psychiatric Morbidity Survey evidence. (July 2017) - Hassiotis, A.; Noor, M.; Bebbington, P.; Afia, A.; Wieland, J.; Qassem, T.
Summary: Borderline intellectual functioning (BIF) is associated with several neuropsychological deficits. We used national data to establish the prevalence of psychosis and psychotic symptoms, and the role of potential mediators. The BIF group were more than twice as likely to have probable psychosis (adjusted odds ratio (OR) = 2.3, 95% CI 14−4.0) and to report hallucinations (adjusted OR = 2.9, 95% CI 1.9−44) but not persecutory ideation. Salient mediators were depressive symptoms and the cumulative total of life events. Our findings suggest mechanisms other than drug use that are contributing to the strong relationship between BIF and severe mental illness and that may be amenable to treatment.